Effects of single or combination of dietary vitamin C and β-glucan supplementation on golden trevally, \(Gnathanodon speciosus\) (Carangidae) - Do Huu, Hoang; Huynh, Sang Minh; Nguyen, Thi Nguyet Hue; Vo, Hai Thi; Tran , Thi Minh Hue; Huynh, Thi Ngoc Duyen; Nguyen, Tam Vinh (Vietnam Journal of Marine Science and Technology, 2024)
This study aims to test the single and combination effects of dietary vitamin C and β-glucan on golden trevally, Gnathanodon speciosus. The basal diet (D0) was added with vitamin C at 200 mg kg-1 diet (D1), β-glucan at 1.0 g kg-1 diet (D2), and a combination of vitamin C and β-glucan (200 mg vitamin C and 1 g β-glucan per kilogram diet) (D3). The diets were fed the fish for eight weeks. After eight weeks of diet feeding, the growth rate of the fish enhanced significantly with the presence of vitamin C, β-glucan, and the combination of Vitamin C and β-glucan (p < 0.05). The growth rate was significantly higher in a fish-fed diet combined with vitamin C and β-glucan. Survival rates were not significantly different among diet treatments. Muscle protein of fish ranged from 18.36–21.50% among diet treatments. Fish protein content in fish was not influenced by vitamin C, but the protein was higher in fish fed with the β-glucan-added diet and combination the β-glucan and vitamin C-added diet. The current results suggest that a supplemented combination of vitamin C and β-glucan could boost this golden trevally’s growth and body composition at the juvenile stage.